3E mini aquaponic - Hanuar, Muhammad Naqib Afiq; Khamis, Ahmad Hakim; Sha’izan, Mohamad Syahmeer; Suwandi, Siti Rafhanah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
3E MINI AQUAPONIC is our project name which we want to introduce The Revolution for Digitalize Agriculture. The concept of this innovation is 3E which is Environmentally, Easy, and Empowering. Aquaponic is an agricultural technology that combines aquaculture which is activities of water animal husbandry with hydroponic activities which is plant cultivation without soil medium but by water medium like kale, spinach, and chili in an integrated system. The important element in aquaponics is fish, plant, and bacteria. All three elements will form a reciprocal cycle of beneficial or mutualistic symbiosis. Our country always faces a main problem which is water pollution which has caused serious problems in our country and harms the sustainability of our water resources. Besides, the other problem is excessive use in agriculture is the main cause of freshwater shortage and can increases pollution. The objective of this innovation is to overcome problems if water pollution occurs to maintain agriculture and irrigation and to introduce an aquaponic system. Besides, giving knowledge of the aquaponic process and its advantages. The advantages of aquaponic for the environment are water and nutrients are recycled in an economical closed-loop manner water, protects our rivers & lakes which is no harmful fertilizers run into the water, and soil conservation which it can grow six times more than traditional agriculture.